1981
DOI: 10.1021/j150626a034
|View full text |Cite
|
Sign up to set email alerts
|

Temperature programmed desorption study of water adsorbed on metal oxides. 2. Tin oxide surfaces

Abstract: These comparisons suggest that the low value of k2"/k, for reaction of pNPDPP with OHis caused by a relatively deeper penetration of this substrate into the micelle as compared with that of DNCB. A similar conclusion has been made for reactions in functional micelles.53 Values of kz"/kw for reactions of DNCB with phenoxide ion and pNPDPP with aryloxide and oximate ions are close to ~n i t y , 3~~p~~v~~ probably because the hydrophobicities of substrates and nucleophiles are such that both reside in the same re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(70 citation statements)
references
References 4 publications
5
62
1
Order By: Relevance
“…It is assumed that during water addition surface hydroxyls will be formed first; as soon as the surface is saturated, molecularly adsorbed water starts to build up. This pattern of water uptake on the surface was observed on a-A1203 [ 161,TiO,[ 17,341 and SnO,[ 181. To verify this hypothesis TGA profiles of a 15 wt.-% Mn/Al,O, catalyst after water addition at 323 K during different exposure times were compared; see Fig. 10.…”
Section: Deactivation By Watermentioning
confidence: 69%
“…It is assumed that during water addition surface hydroxyls will be formed first; as soon as the surface is saturated, molecularly adsorbed water starts to build up. This pattern of water uptake on the surface was observed on a-A1203 [ 161,TiO,[ 17,341 and SnO,[ 181. To verify this hypothesis TGA profiles of a 15 wt.-% Mn/Al,O, catalyst after water addition at 323 K during different exposure times were compared; see Fig. 10.…”
Section: Deactivation By Watermentioning
confidence: 69%
“…metal oxide surfaces takes instead place at 473 K). 39 Similarly, we can exclude that the surface conductivity is due to the motion of the sodium species, as it has been shown that the sodium atoms remain tightly bound to the fullerene molecules up to at least 575 K. 14 A more likely explanation is that the surface-enhanced conductivity is due to charge propagation by hydrogen-bond exchange (proton-shuttling) between intact, physisorbed water molecules in higher hydration layers.…”
Section: B1 Effect Of the Surface Hydrationmentioning
confidence: 99%
“…Once this initial layer formed, it is no further affected by exposure to humidity. In the case of anatase, which is the phase of our titania sensors, it has been estimated that the desorption of the chemisorbed layer takes place around 200 • C [19].…”
Section: Basic Models Assumed For the Electrical Conduction And Polarmentioning
confidence: 99%